Residual Pure Intralymphatic Breast Carcinoma Following Neoadjuvant Chemotherapy Is Indicative of Poor Clinical Outcome, Even in Node-Negative Patients. (September 2017) - Cheng, Esther; Ko, David; Nguyen, Michaela; Moo, Tracy-Ann; Andreopoulou, Eleni; Hoda, Syed A.; D'Alfonso, Timothy M.
Abstract : Residual carcinoma confined to lymphovascular spaces following neoadjuvant chemotherapy (NAC) for invasive breast carcinoma is an uncommon finding. We studied pathologic features and outcome for patients with pure intralymphatic carcinoma (PIC) following NAC, a pattern of residual disease reported to have a poor outcome in the only previously published series of this entity. Six of 284 (2.1%) patients treated with NAC were studied. All 6 patients had axillary lymph node involvement before NAC. Tumors were triple-negative (n=3) and HER2+ (n=3: 2 ER+, 1 ER−). Two patients presented with clinical findings of inflammatory carcinoma. Three of 5 pre-NAC core biopsies showed lymphovascular invasion. Three patients showed complete clinical response to NAC, and 3 showed partial response. Post-NAC surgical specimens showed foci of intralymphatic carcinoma in the breast spanning an extent of 0.5 mm to 0.5 cm. Residual ductal carcinoma in situ was present in 2 cases. Four of 6 patients converted to node-negative following NAC. One patient had distant metastasis at presentation and 1 patient died of pulmonary embolism 2 months after surgery. Three of the 4 remaining patients developed distant metastasis, of which 2 first recurred locally (in mean follow-up of 46.5 mo). Patients with PIC had significant greater risk for relapse (hazard ratio, 10.18 [1.97, 52.58]; P =0.006) compared with other NAC-treated patients, after controlling for residual lymph node involvement, tumor size, tumor subtype, histologic grade, and age. Residual PIC following NAC is associated with poor outcome, including in patients that are node-negative following NAC.